Genetics, cardiac phenotype and cardiovascular outcomes in Fabry disease patients in Finland - Valtola, Kati; Pietilä‐Effati, Päivi; Männistö, Jonna M. E.; Walls, Susanne; Kantola, Ilkka; Kuusisto, Johanna (Wiley, 2026)
Aims
To investigate the genetics, cardiac phenotype and cardiovascular outcomes of Finnish Fabry patients.
Methods and results
Among the 109 patients with Fabry disease (FD) diagnosed in Finland by 2018, 97 (89%; 32 males and 65 females, mean ages 42 and 52 years) were followed for a mean of 12 years. Data on genetics, phenotypes, cardiac imaging and cardiovascular outcomes were collected from the Fabry Registry and medical records. The 26 families with FD harboured 22 different hemi-/heterozygous GLA variants, most commonly p.R227X, p.A143T or p.P409A. The Fabry phenotype in males was classic in 19 (59%), late-onset in 10 (31%) and intermediate in 3 (9%) patients. Among the females, 62 (95%) were symptomatic. Fabry cardiomyopathy (FC, maximal left ventricular wall thickness >= 13 mm, or an increased cardiac mass and decreased T1 time, or typical late gadolinium enhancement (LGE) in CMR) was present in 21 (66%) males manifesting since their 20s, and in 32 (49%) females since their 40s. LGE in CMR was detected in most subjects with cardiomyopathy, particularly in females. Among the 53 patients with FC, 16 (30%) developed atrial fibrillation, 17 (32%) stroke, 14 (26%) heart failure (HF) and 3 (6%) end-stage renal disease. Nine patients died during the follow-up at mean ages of 48 (males) and 75 years (females), three of whom died from HF and three from stroke. Eight of those who died had cardiomyopathy.
Conclusions
In Finland, FD is caused by multiple GLA variants. Classic phenotype is more common. Contrasting previous studies, most women are symptomatic. Cardiomyopathy is very common also in women since their 40s and associates with atrial fibrillation, HF, stroke and death, emphasizing the malignant natural course of FC. Our findings highlight the need for even more diligent monitoring of cardiac manifestations also in females with FD by regular cardiac imaging with CMR.